WATERCOLOR PAINTING TECHNIQUES - Jabbarov Botirsher Gulomovich (Web of Journals Publishing, 2024)
In this article, taking into account the work of the students of the 2nd level of the 60111200 -Fine arts and engineering graphics education field of higher educational institutions in watercolor, which is the main imaging tool of painting science, the author describes watercolor and its components, history, methods of working with easel painting, as well as thinner, brush, palette, discusses the information students need to use basic tools such as mastic.
Keywords: painting with a painting device, eye paint, inorganic substance, linseed oil, thinner, canvas, cardboard, metal, wood, primer, pencil, palette knife, alla prima, lightening, still life composition, portrait, human figure, harmony, stability, spatiality .